Pengaruh Panjang Kolom Distilasi Bahan Isian Terhadap Hasil Produk Cair Sampah Plastik - Isti Nur Azizah; Ninda Puspita Sari; Maryudi Maryudi (CHEMICA: Jurnal Teknik Kimia, 2016)
Plastic waste is a problem that has to be taken seriously for the pollution of the environment, especially for land contamination. For now, the handling of plastic waste is normally disposed (landfills), burned, or recycled (recycle). The burning of plastic waste is usually carried out by the pyrolysis method to produce plastic oil. To get the maximum results needed further analysis in the form of purification by distillation, where the distillation is a method that can be used for advanced analysis, one with a distillation column. Fractional distillation often called the distillation column is to separate liquid components, two or more, of a solution based on differences in their boiling points. This distillation can also be used to mix with a boiling point of less than 20°C and work at atmospheric pressure or low pressure. Application of this type is used in the distillation of crude oil industry, to separate the components in the crude oil distillation Differences simple fractionation and distillation is the fractionation column. In this column, warming occurs gradually with different temperatures on each license plate. Different heating is intended for refining distillates from the plates underneath. Getting to the top, the less volatile liquid. The distillation process depends on the characteristics of the vapor pressure of a liquid mixture of components.The distillate was obtained at a temperature of 195oC, 200oC, 220oC, 235oC, and 240oC and the most products component of pyrolysis plastic in previous research was obtained at 195oC, 200oC, and 220oC